Judicial Perspectives on the Equitable Resolution of Anti-SLAPP Cases: Insights from Indonesia - Rachmawaty, Rachmawaty; Gunawan, Matthew Marcellinno; Nurviani, Novi (Journal of Law, Environmental and Justice, 2024)
This research examines Indonesian judges' views on Anti-SLAPP case settlement and their philosophical approach. This research prescribes doctrine. The research shows that the judge's Pancasila-based Anti-SLAPP judgement needs to be revised. When the community raises environmental concerns, the practice repeats. The community will be punished in whatever way is necessary to eliminate participation. Development that harms the environment but enriches the government and corporations will continue. Based on these facts, it is known that the regulation and application of Anti-Slap in Indonesia are still being made to provide justice for all elements due to limited regulation. The lack of legal protection for environmental fighters in Indonesia shows why judges' rulings are not founded on Pancasila justice. The five Pancasila precepts guide courts' anti-SLAPP dispute resolution. A judge's ruling that exhibits legal certainty helps find the proper law while resolving court matters. Judges must consider customary and unwritten social laws when making decisions because the law may not regulate.